PENGEMBANGAN KOMPETENSI SOSIAL SANTRI MELALUI MANAJEMEN KURIKULUM KEMASYARAKATAN PESANTREN - Ahmad Muhajir; Abdul Goffar; Agus Fawait (TAZKIRAH, 2026)
This study aims to analyze the management of community-based curriculum in developing students’ social competence at Nurul Huda Islamic Boarding School, Situbondo. The study employs a qualitative approach using a field research design. Data were collected through observation, in-depth interviews, and documentation involving the pesantren leader, administrators, teachers, and students as informants. Data analysis was conducted using descriptive-analytical procedures, including data reduction, data display, and conclusion drawing. The findings indicate that the community-based curriculum is managed in an integrated manner through needs-based planning, structured role organization, implementation of socio-religious practices, and continuous evaluation. Programs such as Yāsin memorization, tahlil, Friday Qur’anic recitation, bilal training, tarawih nidā’, khutbah, and tarhim significantly contribute to the development of students’ social competence, particularly in religious communication, leadership, and social responsibility. This study concludes that community-based curriculum management plays a strategic role in Islamic Education Management in preparing students to actively participate in community life.